Round-Trip Emergency Supply Distribution Model Based on Nonfixed Routes - Yanli Tang; Ying Xiong; Ying Chen (Journal of Advanced Transportation)
In the face of increasing natural or man-made disasters, rapid and effective emergency dispatch and organization are of great significance to ensure the life safety of people and reduce social losses. In view of the long duration, strong demand urgency, and relatively limited transportation capacity after catastrophic events, this paper proposes a round-trip emergency supply distribution model based on nonfixed routes. This model includes two main features: (1) round trip: emergency vehicles can travel back and forth to distribute supplies; (2) unfixed routes: distribution routes of the same emergency vehicle could be variable in different trips. In order to ensure the timeliness and fairness of the supply distribution scheme, the model objective function is set to minimize the total supplies’ waiting time at all demand points. According to model features, 4 constraints are set, including flow balance, capacity, vehicle scheduling, and time window. On this basis, a compound algorithm combining 2-opt and tabu search is designed to obtain the optimal plan of the model. To verify the effectiveness and superiority of the model and solution method, a case study based on the Sioux Falls network is carried out. Compared with the traditional method, the objective function is optimized by 11.92%. In fact, under the control of multiple constraint conditions, the model well fits the actual application scenarios, which can provide theoretical guidance and decision support for the distribution of relevant emergency supplies.